2020
DOI: 10.1016/j.agee.2019.106687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tillage and N fertilization rate on soil N2O emissions in irrigated maize in a Mediterranean agroecosystem

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 3.0 de Creative Commons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 52 publications
5
13
0
Order By: Relevance
“…The high NH 4 + and NO 3 − concentrations following fertilization directly provide sufficient substrates for nitrification and denitrification and thus significantly stimulate soil N 2 O emissions [8,11,20,23]. This phenomenon has been reported in many previous studies on different croplands [5,10,43]. On average, pulse N 2 O emissions following fertilization accounted for 67% of the annual cumulative N 2 O fluxes (Figure 4).…”
Section: Factors Regulating the Increased Soil N 2 O Emissions Inducesupporting
confidence: 63%
“…The high NH 4 + and NO 3 − concentrations following fertilization directly provide sufficient substrates for nitrification and denitrification and thus significantly stimulate soil N 2 O emissions [8,11,20,23]. This phenomenon has been reported in many previous studies on different croplands [5,10,43]. On average, pulse N 2 O emissions following fertilization accounted for 67% of the annual cumulative N 2 O fluxes (Figure 4).…”
Section: Factors Regulating the Increased Soil N 2 O Emissions Inducesupporting
confidence: 63%
“…Agricultural practices can be related to N 2 O emission based on crop yield, referred to as yield-scaled N 2 O emission (YSNE). There are many studies observed the effect of tillage operations and N fertilization on N 2 O emission in the arable land [17][18][19][20][21]. Therefore, the objective of this study was to determine the effects of different tillage operations and N fertilizations on N 2 O emission and crop yield from upland soil.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Next Generation Sequencing (NGS)-based OMICS technologies provided better insight into the crucial roles of rhizosphere microbiomes towards soil and plant genetic traits under varying conditions [ 33 , 36 , 37 ]. Comprehensive research has not yet been carried out in lentil towards deciphering the genotype-dependent microbiome diversity along with the studies on additional changes in the soil geochemical reactions towards availability of important nutrients for plant growth.…”
Section: Introductionmentioning
confidence: 99%